Ascophyllum nodosum Seaweed Extract Alleviates Drought Stress in Arabidopsis by Affecting Photosynthetic Performance and Related Gene Expression - Santaniello, Antonietta; Scartazza, Andrea; Gresta, Francesco; Loreti, Elena; Biasone, Alessandro; Di Tommaso, Donatella; Piaggesi, Alberto; Perata, Pierdomenico (Frontiers in Plant Science, 2017)
Drought represents one of the most relevant abiotic stress affecting growth and yield of crop plants. In order to improve the agricultural productivity within the limited water and land resources, it is mandatory to increase crop yields in presence of unfavorable environmental stresses. The use of biostimulants, often containing seaweed extracts, represents one of the options for farmers willing to alleviate abiotic stress consequences on crops. In this work, we investigated the responses of Arabidopsis plants treated with an extract from the brown alga Ascophyllum nodosum (ANE), under drought stress conditions, demonstrating that ANE positively influences Arabidopsis survival. Pre-treatment with ANE induced a partial stomatal closure, associated with changes in the expression levels of genes involved in ABA-responsive and antioxidant system pathways. The pre-activation of these pathways results in a stronger ability of ANE-treated plants to maintain a better photosynthetic performance compared to untreated plants throughout the dehydration period, combined with a higher capacity to dissipate the excess of energy as heat in the reaction centers of photosystem II. Our results suggest that drought stressed plants treated with ANE are able to maintain a strong stomatal control and relatively higher values of both water-use efficiency (WUE) and mesophyll conductance during the last phase of dehydration. Simultaneously, the activation of a pre-induced antioxidant defence system, in combination with a more efficient energy dissipation mechanism, prevents irreversible damages to the photosynthetic apparatus. In conclusion, pre-treatment with ANE is effective to acclimate plants to the incoming stress, promoting an increased WUE and dehydration tolerance.